Linear transceiver design with intercarrier interference reduction for multiple-input–multiple-output with orthogonal frequency division multiplexing systems - Qian, Fengyong; Leung, Shu-hung; Mai, Ruikai; Zhu, Yuesheng (IET communications, 2014)
In this study, a joint design of precoder and equaliser of a linear transceiver for multiple-input–multiple-output system with orthogonal frequency division multiplexing in the presence of intercarrier interference (ICI) is presented. The matrix structures of the precoder and equaliser are banded for the sake of reducing the computational complexity and feedback overhead from the receiver to the transmitter. The design criterion is to minimise the mean-squared error subject to a total transmitted power constraint of which the power is allocated over space and frequency domains in the precoder. The authors use the Karush–Kuhn–Tucker conditions to derive an iterative procedure to obtain a convergent solution and a closed-form procedure for the optimal full transceiver. Numerical results show that the banded precoder is an efficient scheme to improve the bit error rate (BER) of the transceiver by simply increasing its band size and can provide better BER performance than that of the existing jointly designed full transceiver in the presence of ICI. With small band sizes, the proposed transceiver can give performance close to that of the jointly designed full transceiver but with lower implementation complexity and feedback overhead to the transmitter.